Analisis Pengaruh Kualitas Layanan Aplikasi Mobile JKN Menggunakan Metode E-Servqual Untuk Pengguna Di Kota Jambi - Anastasya, Dwi; Husaein, Ahmad; Aryani, Lies (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2024)
The JKN BPJS Mobile Application is a solution to provide more efficient access to JKN BPJS participants in managing health information and services. The focus of this application is to make it easier for participants to access health services and information, while increasing the Efficiency of health insurance management. The importance of the quality of this application service is the key to a satisfying and effective user experience. According to data on the Play Store, even though the Mobile JKN application has been downloaded more than 10 million times, there is still user dissatisfaction which is reflected in various reviews. Some issues include navigation difficulties, lack of guidance, and difficulty getting support when encountering problems. This research aims to analyze service quality and determine the influence of the quality of the JKN Mobile Application service using the E-Servqual method for users in Jambi City. The E-Servqual method includes 7 variables, namely: Efficiency, Fulfillment, Reliability, Privacy , Responsiveness, Compensation and Contact . Data was taken by distributing questionnaires to 400 respondents who were users of the JKN Mobile Application in Jambi City. Data management in this research uses IBM SPSS version 25.0 software. The results of this research show that of the seven E-Servqual variables, four variables have a significant effect, namely the Efficiency, Fulfillment, Privacy and Contact variables, while the Reliability, Responsiveness and Compensation variables do not have a significant effect on User Satisfaction.